Harvest, manipulation and commercialisation systems of pomegranate (Punica granatum L.) - Muñoz J.A. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
The aim of the present work is to illustrate from a personal viewpoint (as manager of an agricultural processing firm) a pomegranate elaboration process from harvest to the national and international market distribution.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)